Trade in genetically modified food: a survey of empirical studies - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
New advances in biotechnology have enhanced production of maize, soybeans, and cotton. Consumer reactions to the new technology have been mixed. Both the supply shock, from an increase in productivity or a reduction in input use, and the demand shock, which is determined by the consumer response to consuming GM foods, affect production, trade, and prices of GM foods. In this paper, we survey models that analyze the market effects of GM technology. The results depend on a number of important issues such as the cost of market segmentation and labeling, the nature of the productivity shock to producers of GM products, and the extent of any adverse reaction to GM products by consumers. The results from global trade models indicate that, if costs of labelling and market segmentation are not large, world markets can adjust to the various scenarios without generating extreme price differentials between GM and non-GM commodities or extreme changes in the pattern of world production and trade. Through market linkages, the benefits of the new technology tend to be spread widely, with adopters generally gaining more than non-adopters. In particular, developing countries will benefit if they can adopt the new technologies, and get mixed results if they are non-adopters. -- Authors' Abstract